Effect of woven fabric structure on the air permeability and moisture management properties. Issue 5 (3rd May 2016) - Umair, Muhammad; Hussain, Tanveer; Shaker, Khubab; Nawab, Yasir; Maqsood, Muhammad; Jabbar, Madeha
Abstract : In this study, six different woven samples were produced on air jet loom with two different weave designs (i.e. 3/1 twill and 1/1 plain), three different picking sequences (i.e. single pick insertion (SPI), double pick insertion (DPI) and three pick insertion (3PI)). All the woven samples were singed, desized, bleached and finished together at industrial scale, as a single lot. The effect of these factors on the wetting, wicking and air permeability (AP) of the fabric samples was analysed. It was revealed that the fabric weave design and picking sequence has statistically significant effect on fabric wetting time, water spreading speed and AP of the fabric. It was found that fabrics woven in twill weave design and with simultaneous 3PI give significantly better AP, shorter wetting time and better water spreading rate as compared to plain woven fabrics and those with double or SPI. It could be concluded that the thermophysiological comfort of woven fabrics may be significantly improved simply by selecting a suitable weave design and picking sequence.